Dental and Medical Students’ Knowledge and Attitude toward COVID-19: A Cross-Sectional Study from Pakistan - Ali, Saqib; Alam, Beenish Fatima; Farooqi, Faraz; Almas, Khalid; Noreen, Sara (European Journal of Dentistry, 2020)
Objective The aims of this study were to investigate the awareness, knowledge, and attitudes of Pakistani medical and dental undergraduate students toward COVID-19 during the surge of its outbreak.Materials and Methods The multicentered, cross-sectional study was carried out nationwide among undergraduate medical and dental students. A convenience sampling technique was used. A self-developed online questionnaire was pretested to be completed by the participants. It was distributed using social media. The survey was comprised of questions related to demographics, health status, general hygiene perception, understanding, and the learning attitudes of the students. Comparisons of the knowledge scores and the attitude responses with the demographic information were done using the independent t-test, one-way ANOVA, and Chi-square, as appropriate.Results Of the 937 total respondents, 353 (38%) were males and 582 (62%) were females; two students did not mark their gender. Of these, 680 (73%) were dental students and 257 (27%) were medical students. The mean knowledge score of the female dental students (5.15 ± 1.08) was significantly higher than that of the male students (4.87 ± 1.09). Overall, the mean knowledge score was statistically higher among the medical students in comparison to the dental students (5.21 ± 1.15, 5.05 ± 1.09; p = 0.054), respectively.Conclusion The medical and dental students were both aware of the importance of the use of a mask. The medical students had a greater awareness regarding the mode of transmission, symptoms, and origin of COVID-19. However, the dental students showed better understanding of the use of surgical masks and the correct protocol for hand washing. Social media was considered the main source for COVID-19 related information.
Keywords: attitude; awareness; COVID-19; knowledge; Pakistan; students